2011
DOI: 10.5004/dwt.2011.2402
|View full text |Cite
|
Sign up to set email alerts
|

Closed circuit desalination — A new low energy high recovery technology without energy recovery

Abstract: ab s t r ac tClosed circuit desalination of Mediterranean water with 47.5±1.5% recovery was demonstrated in the RO energy range 1.85-2.25 kWh/m 3 for the respective flux range 6-18 lmh with head element recovery of 7.0±0.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 1 publication
2
32
0
4
Order By: Relevance
“…In terms of irreversibilities, the energy costs associated with losses in the RO module, the high pressure pump and the chemical energy in the brine are most significant. Losses in the RO module can be reduced through staging and/or batch processing [48]. Losses in the high pressure (HP) pump can be reduced through the use of higher performance pumps or enhanced energy recovery [36,49].…”
Section: 445mentioning
confidence: 99%
“…In terms of irreversibilities, the energy costs associated with losses in the RO module, the high pressure pump and the chemical energy in the brine are most significant. Losses in the RO module can be reduced through staging and/or batch processing [48]. Losses in the high pressure (HP) pump can be reduced through the use of higher performance pumps or enhanced energy recovery [36,49].…”
Section: 445mentioning
confidence: 99%
“…The recently emerging new closed circuit desalination (CCD) technology [2][3][4][5][6][7][8][9][10][11] of high-recovery and low-energy BWRO irrespective of the number of elements per module is noteworthy in particular in the context of small compact units for diverse applications, a subject matter to be discussed hereinafter. The BWRO-CCD technology [3,7,10] takes place by internal concentrate recycling with occasional replacement of brine by fresh feed and is characterized by high-recovery, low-energy consumption without need of energy recovery, reduced fouling (scaling and/or biofouling) and flexible control.…”
Section: Introductionmentioning
confidence: 99%
“…The fi rst paper in this series [5] describes the theoretical principles of CCD and exemplifi es the process with SWRO-CCD trials carried out with Mediterranean Water (4.1%) using an apparatus with four modules (M) each of four elements (E) -4ME4 confi guration. The trials results revealed RO energy of 1.85-2.25 kWh m −3 for 47.5 ± 1.5% recovery in the respective fl ux range 6-18 lmh with head element recovery of 7.0 ± 0.5%.…”
mentioning
confidence: 99%